Five-parameter intervariant boundary characterization of martensite in commercially pure titanium. (1st August 2018) - Farabi, Ehsan; Hodgson, Peter D.; Rohrer, Gregory S.; Beladi, Hossein
Abstract: The intervariant boundary characteristics of a commercially pure Ti microstructure formed by the β → α martensitic phase transformation were described according to the crystallography of the displacive transformation and the boundary plane orientation. The martensitic transformation created a microstructure whose grain boundary misorientation angle distribution had four distinct peaks that were consistent with the misorientations between the variants produced by the Burgers orientation relationship. Interestingly, about 60% of population corresponded to 60°/ [ 11 2 ¯ 0 ] intervariant boundaries. Three-variant clusters with a triangular morphology were observed frequently. This configuration is consistent with the phenomenological theory of martensite, which predicts that these clusters, separated by 60°/ [ 11 2 ¯ 0 ] boundaries, have a lower transformation strain than other possible variant cluster arrangements. Other intervariant boundaries resulted from the impingement of different combinations of distinct three-variant clusters. The five-parameter boundary analysis revealed a strong anisotropy in the plane orientation distribution, showing that boundaries have a tendency to terminate on prismatic { h k i 0 } and pyramidal { 10 1 ¯ 1 } planes, when misorientation was ignored. The dominant 60°/ [ 11 2 ¯ 0 ] intervariant boundaries had symmetric tilt ( 1 ¯ 101 ) boundary planes, which are a low energy configuration. Graphical abstract: Image 1